New Fundraisers : Who organises charitable giving in contemporary society? - Breeze, Beth (Policy Press, 2017)
Charitable fundraising has become ever more urgent in a time of extensive public spending cuts. However, while the identity and motivation of those who donate comes under increasingly close scrutiny, little is known about the motivation and characteristics of the 'askers', despite almost every donation being solicited or prompted in some way. This is the first empirically-grounded and theorised account of the identity, characteristics and motivation of fundraisers in the UK. Based on original data collected during a 3-year study of over 1,200 fundraisers, the book argues that it is not possi.